Digital agriculture platforms: Understanding innovations in rural finance and logistics in Uganda’s agrifood sector - Ajambo, Susan; Ogutu, Sylvester O.; Birachi, Eliud Abucheli; Kikulwe, Enoch Mutebi (International Food Policy Research Institute, 2022)
Agriculture is the mainstay of Uganda’s economy, contributing about 25% of the GDP, a third of the export earnings and almost all the country’s food requirements. Yet, the sector still faces various challenges that affect production and the income derived from it. Systemic issues impact smallholder farmers' livelihoods across markets, land, skills, and capital, with cross-cutting social exclusion issues. Effective application of digital agricultural technologies has emerged as a catalyst in addressing productivity and efficiency challenges and enhancing inclusiveness in agri-food systems. Digital technologies have shown potential to address bottlenecks in access to extension services, marketing systems, suitable financial products, reliable weather information, transport services and logistics as well as supply chain management. Scaling of digital agricultural technologies in Uganda is critical for improving productivity and addressing challenges in the agricultural sector. However, for scaling to be undertaken effectively and inclusively, there is need to address the barriers that limit the use of digital innovations for some populations. However, the issues surrounding scaling and inclusivity of digital services are not well understood. This study therefore sought to contribute to bridging this knowledge gap through an assessment of the existing digitally enabled innovative cross-value chain services to gain insights into how the services are addressing inefficiencies, creating opportunities for improving efficiency and inclusiveness as well as identifying promising innovations for scaling. Specifically, the study focused on innovations in finance and logistics for value chains. For finance, the study specifically looked at digital payments, credit, and insurance, while for logistics, the focus was on supply chain management, transportation, traceability, digital platforms for e-commerce, and (cold) storage across value chains. The study used a qualitative approach to collect data in two phases: the first phase involved conducting an inception workshop followed with key informant interviews with 39 service providers and enablers. The second phase involved case studies using 12 Focus Group Discussions (FGDs), 12 individual interviews and a validation workshop. The findings show potential for digital agricultural innovations to address some of the challenges. Several benefits are associated with the current use of digital innovations including linking value chain actors with the enabling services (e.g., insurance companies, banks, government), increased access to markets, access to extension and advisory services including market and weather information and quality agri-inputs and tractor services, services such as credit and savings, agri-insurance, agri-trucking, Heating Ventilation and Conditioning (HVAC) and warehousing. The use of digital innovations has for instance enabled access to agri-insurance and digital loans or credit which was not possible before. However, there are some challenges with the use of digital finance and logistic services. For instance, the study identified challenges of access due low awareness and information due to limited digital literacy, social norms and power-relations that disadvantage some sections of the population such as the women and youth from access and some technology design issues that need to be addressed for effective and inclusive uptake and scaling. Additionally, the ICT infrastructure in Uganda is unevenly distributed with significant gaps between rural and urban connectivity. Communication infrastructure (e.g., network coverage and broadband services) is established in urban centers, but rural areas have poor or no connectivity. Limited access to electricity is a major cause of the discrepancies in urban–rural Internet use and mobile phone penetration rates in Uganda. Yet mobile technology is at the heart of the digital transformation in Uganda as in most parts of sub-Saharan Africa. The study also identified some promising innovations that offer opportunities for scaling, following prioritization by stakeholders of the most significant challenges to scaling (low awareness of services and lack of information to support farmers to make a case for investing in digital services). These innovations have active SMEs and start-ups engaged in them and include digital input supplies and payments bundled with agronomic advisories, e-market places for outputs bundled with digital payments services and logistics, and agricultural logistics services involving transport and warehousing services.